The Effect of Banana Pell (Musa paradisiaca L) Ethanol Extract on The Blood Glucose Level of Diabetic Mice with Alloxan Induction - Jazilah, Nur; Fifteen Aprila Fajrin; Hidayati, Sholihatil; Usman, Mohammad Rofik (Universitas Muhammadiyah Surakarta, 2024)
Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion, insufficient insulin hormones, or the inability to use insulin effectively. One of the traditional medicine use with DM is to control their blood glucose levels using herbal plants, namely the banana peel plant (Musa paradisiaca L.) which is rich in flavonoids, alkaloids, and tannins. This study aims to determine the effect of ethanol extract banana peel EEBP on glucose levels in mice with alloxan induction. The design of this study was a laboratory experiment, using male white mice (Mus musculus L) Balb/c strain, which were induced with alloxan at a dose of 200 mg/kg.bw. The mice were divided into six groups, namely normal, negative (CMC Na 0.5%), positive (glibenclamide 5 mg/kg.bw), and three groups of EEBP at a dose of 100 mg/kg.bw, 200 mg/kg.bw, and 400 mg/kg.bw. Blood glucose levels were evaluated on day 3 after induction, as well as day 7 and 14 after treatment. Blood glucose level data were analyzed using one-way ANOVA, followed by LSD post hoc test with 95% confidence level. The 400 mg/kg.bw dose of banana peel ethanol extract showed the highest percentage reduction in blood glucose levels, namely 65.83% ± 0.800, compared to other doses. Based on LSD statistical test, doses of 200 mg/kg.bw and 400 mg/kg.bw of EEBP showed no significant difference compared to the positive control (p>0.05). The optimal dose for reducing blood glucose levels in DM mice induced by alloxan is the treatment of EEBP in doses of 200 mg/kg.bw and 400 mg/kg.bw